2017
DOI: 10.3892/etm.2017.5637
|View full text |Cite
|
Sign up to set email alerts
|

Berbamine induces SMMC-7721 cell apoptosis via upregulating p53, downregulating survivin expression and activating mitochondria signaling pathway

Abstract: Hepatocellular carcinoma (HCC) is a primary malignancy in the liver, which is a global health problem. The present study aimed to observe the apoptotic effects of berbamine on SMMC-7721 cell lines and to investigate the effects of berbamine on induction of the intrinsic apoptotic pathway. The human HCC SMMC-7721 cells were cultured and cell morphology observed using a phase contrast microscope. SMMC-7721 cell apoptosis was examined by employing a flow cytometry assay. The nuclei of SMMC-7721 cells were stained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 37 publications
3
17
0
Order By: Relevance
“…As reported here, BBM is effective in inhibiting the growth of cancer cells with induction of the apoptosis of cancer cells. 12 , 20 Moreover, BBM shows significant potential to sensitize cancer cells to radiation therapy, which suggests that BBM maybe a novel radiosensitizer for the treatment of cancer. Previous studies reported the anticancer effect of BBM against a series of tumors including solid tumors and leukemia.…”
Section: Discussionmentioning
confidence: 99%
“…As reported here, BBM is effective in inhibiting the growth of cancer cells with induction of the apoptosis of cancer cells. 12 , 20 Moreover, BBM shows significant potential to sensitize cancer cells to radiation therapy, which suggests that BBM maybe a novel radiosensitizer for the treatment of cancer. Previous studies reported the anticancer effect of BBM against a series of tumors including solid tumors and leukemia.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that the antitumor effects of BBM in a variety of tumors, including breast cancer [19], myeloma [7,20], hepatoma [9,21], prostatic neoplasms [9], pancreatic carcinoma [22] and lung cancer [23]. Jin [22] con rmed that BBM signi cantly downregulated the expression of the antiapoptotic proteins such as Bcl-2 and Bcl-xL and inhibited proliferation in pancreatic carcinoma cells.…”
Section: Discussionmentioning
confidence: 97%
“…It has been reported to possess the effects of anti-oxidation, immunoregulation, and anti-arrhythmia in recent studies [4][5][6][7]. BBM was also revealed to have potential function of antitumor [8][9][10]. However, there were few studies on the anti-tumor effect of BBM in lung cancer,and the in vitro studies just evaluated the cell activity and migration, and the mechanism involved was just Bcl-2/Bax.…”
Section: Introductionmentioning
confidence: 99%
“…Berbamine can also lead to the loss of MMP in human hepatocellular carcinoma cells (SMMC‐7721). Moreover, berbamine can aggravate the release of Cyt‐c into the cytoplasm by upregulating the level of p53 and bax in cells . Mitochondrial dysfunction is a very important link and target in the toxic mechanism of MC‐LR.…”
Section: Discussionmentioning
confidence: 99%